Study of the effects of mineral salts on the biofilm formation on polypropylene fibers using three quantification methods - Bystrianský, Lukáš; Hujslová, Martina; Gryndler, Milan (Folia microbiologica, 2021)
The microbial biofilms are ubiquitous in nature and represent important biological entities that affect various aspects of human life. As such, they attracted considerable attention during last decades, with the factors affecting the biofilm development being among the frequently studied topics. In our work, the biofilm was cultivated on the surface of polypropylene fibers in a nutrient medium inoculated by the suspension of two unsterile soils. The effects of ionic strength and valence of salt on the amount of the produced biofilm and on composition of biofilm microbial communities were investigated. The effect of valence was significant in some OTUs: Arthrobacter/Pseudarthrobacter/Paenarthrobacter and Bacillus with positive response to monovalent salt (KCl) and Streptomyces, Lysinibacillus, Pseudomonas, and Ensifer with positive response to divalent salt (MgSO4). The significant preference for a certain concentration of salts was observed in the case of OTUs Agrobacterium, Bacillus (both 100 mM), and Brevundimonas (30 mM). A new quantification method based on measuring of oxidizable organic carbon in biofilm biomass, based on dichromate oxidation, was used. We compared the results obtained using this method with results of crystal violet destaining and measuring of extracted DNA concentration as proxies of the biofilm biomass. The dichromate oxidation is simple, inexpensive, and fast, and our results show that it may be more sensitive than crystal violet destaining. The highest biomass values tended to associate with high concentrations of the divalent salt. This trend was not observed in treatments where the monovalent salt was added. Our data confirm the importance of inorganic ions for biofilm composition and biomass accumulation.
Keywords: Biomass; bakteriologické techniky; Bacteriological Techniques; Microbiota; Culture Media; půdní mikrobiologie; Minerals; mikrobiota; Salts; kultivační média; Bacteria; Polypropylenes; Soil Microbiology; minerály; biofilmy; polypropyleny; soli; biomasa; Biofilms